2006
DOI: 10.2458/azu_jrm_v59i3_jacobo
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Grazing Effects on Rangeland Vegetation at a Farm Scale

Abstract: We evaluated the adequacy of rotational grazing to improve rangeland condition in the Flooding Pampa region, eastern Argentina, comparing the floristic composition dynamic of the 2 main plant communities under rotational and continuous grazing over a study period of 4 years (1993)(1994)(1995)(1996). The experiment was conducted in commercial farms located in 4 sites of the Flooding Pampa region. In each site, a couple of farms, one managed under rotational grazing (implemented in 1989) and an adjacent one mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 23 publications
1
25
0
5
Order By: Relevance
“…Comparing the benefits of continuous vs. rotational grazing on grassland quality and livestock production Rotational grazing has been claimed to improve forage yield and quality, and maintain pasture species diversity, because farmer control of grazing frequency and duration, allows beneficial plants to recover without repeated selective grazing of preferred plants (Jacobo et al 2006, Briske et al 2011, Sanderman et al 2015. The results of this study showed that grassland quality and livestock production were not influenced by grazing regime (i.e., by neither rotational nor continuous grazing), but that precipitation, temperature, also stocking rate, are the driving factors.…”
Section: Comparing the Benefits Of Grazing Exclusion Vs Grazing On Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the benefits of continuous vs. rotational grazing on grassland quality and livestock production Rotational grazing has been claimed to improve forage yield and quality, and maintain pasture species diversity, because farmer control of grazing frequency and duration, allows beneficial plants to recover without repeated selective grazing of preferred plants (Jacobo et al 2006, Briske et al 2011, Sanderman et al 2015. The results of this study showed that grassland quality and livestock production were not influenced by grazing regime (i.e., by neither rotational nor continuous grazing), but that precipitation, temperature, also stocking rate, are the driving factors.…”
Section: Comparing the Benefits Of Grazing Exclusion Vs Grazing On Rmentioning
confidence: 99%
“…In North America, an eightyear grazing trial showed that rotational grazing resulted in greater perennial herbaceous basal area and less bare ground on bottom land soils and clay-loam soils, than the continuously grazed control (Teague and Dowhower 2003). Rotational grazing promoted functional groups composed of high forage value species and reduced bare soil, through the accumulation of litter (Jacobo et al 2006). However, in southeast Australia, a study over 12 yr found that grazing exclusion led to limited changes in vegetation cover, and species composition, because of presumed low site productivity and a high degree of understory degradation (Lunt et al 2007, Schultz et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of intensive grazing and management can lead to soil degradation and invasion by exotic species, which may negatively affect carbon inputs of large fragments. Previous studies in Rio de la Plata grasslands showed that grazing reduces the contribution of the dominant grasses, increases the abundance of subordinate grasses and promotes the invasion of dicotyledonous exotic species, many of them from Asia and Europe (Sala et al 1986;Rusch & Oesterheld 1997;Jacobo et al 2006). As a result of these floristic changes, ANPP is significantly reduced under continuous grazing (Rusch & Oesterheld 1997).…”
Section: Discussionmentioning
confidence: 98%
“…These canopy gaps could be created by flooding events in herbaceous communities (Insausti & Soriano 1995) and then kept open by grazing animals, such as large herbivores (Deregibus et al . 1994; Jacobo et al . 2006).…”
Section: Discussionmentioning
confidence: 99%